(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to examine the mediating role of authentic leadership in the relationship between psychological capital and quality of work life among employees at Al-Amna Hospital. The study adopted a descriptive-analytical approach, and data were collected through a questionnaire distributed to a sample of (118) medical and administrative staff. Data analysis was conducted using SPSS, while Structural Equation Modeling (SEM) was applied using AMOS software. The results revealed high levels of psychological capital, authentic leadership, and quality of work life among the respondents. The findings also indicated significant positive relationships between psychological capital and quality of work life, between psychological capital and authentic leadership, and between authentic leadership and quality of work life. Moreover, the results confirmed that authentic leadership plays a significant mediating role in strengthening the relationship between psychological capital and quality of work life. Based on these findings, the study recommended enhancing authentic leadership practices and developing employees’ psychological capital as effective approaches to improving the quality of work life and overall performance in healthcare institutions.